2016
DOI: 10.1136/bcr-2015-213184
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid adenoma arising within the sternocleidomastoid muscle: a rare complication of autotransplantation

Abstract: A 19-year-old patient presented with slowly enlarging, painless, left-sided cervical mass. She had a background of multiple endocrine neoplasia 2B and had undergone a total thyroidectomy for medullary thyroid carcinoma during childhood. A cervical recurrence was therefore suspected. Ultrasonographic and MRI examination revealed a well-defined lesion within the left sternocleidomastoid muscle. Further evaluation with sestamibi and single-photon emission CT revealed elevated tracer uptake within the lesion. Cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifty-one reports were retrieved and assessed for eligibility. Finally, 40 articles were shortlisted and included in this review 7 - 46 . ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the 40 studies, 139 patients were reported to have CL after head and neck surgeries (26 left neck dissections, 4 right neck dissections, 19 bilateral neck dissections, 85 neck dissections with side unspecified, and 6 patients who underwent other procedures of the neck such as lobectomy, thyroidectomy, or parathyroidectomy) 7 - 46 . ( Table 1 , Supplementary Table 1 )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that there are two well-established risk factors for the development of PTC: previous radiation exposure ( 27 ) and family history ( 28 ). A number of other possible risk factors have been reported, such as elevated TSH levels ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…More than one-third of patients with MEN1 are undiagnosed upon initial operation, and approximately half develop persistent disease after initial operation [24]. Rarer causes of initial failure include parathyromatosis ( Figure 1), parathyroid carcinoma, and adenoma arising from autotransplanted parathyroid glands following surgical exploration (Figures 1 and 2), each accounting for ≤3% of reoperative cases [12,19,25,26]. e development of a second adenoma in a previously normal gland is rare except for in patients with prior neck radiation [27].…”
Section: Common Causes Of Initialmentioning
confidence: 99%